Performance of magnetic resonance susceptibility-weighted imaging for detection of calcifications in patients with hepatic echinococcosis - Müller, Jan; Stojković, Marija; Kauczor, Hans-Ulrich; Junghanss, Thomas; Weber, Tim (Journal of computer assisted tomography, 2018)
Objective: We evaluated the performance of susceptibility-weighted imaging (SWI) for identification of hepatic calcifications in alveolar echinococcosis and cystic echinococcosis. - Methods: The SWI images of 58 lesions in 40 patients (age, 49 ± 14 y) with alveolar echinococcosis (n = 22) or cystic echinococcosis (n = 18) were reviewed for calcifications. First, calcifications were suggested by visual assessment. Second, ratios of minimum intralesional intensity and mean lumbar muscle intensity were recorded. Computed tomography (CT) served as the criterion standard. - Results: Thirty-seven lesions showed calcifications on CT. Susceptibility-weighted imaging provided a sensitivity of 89.2% (95% confidence interval [CI], 50.1-75.7) and a specificity of 57.1% (95% CI, 34.4-77.4) for calcifications detected by visual assessment. Receiver operating characteristic curves demonstrated a sensitivity of 67.6% and a specificity of 85.0% for an intensity ratio of 0.61. A specificity of 100% (95% CI, 80.8-100) and a sensitivity of 84.5% (95% CI, 67.3-93.2) were achieved by SWI for calcifications with a density greater than 184 HU in CT. - Conclusions: Identification of hepatic calcifications is possible with SWI. Susceptibility-weighted imaging offers the potential to reduce the need for of CT imaging for evaluation of echinococcosis.